Total plant performance management : a profit-building plan to promote, implement, and maintain optimum performance throughout your plant - Mobley, R. Keith, 1943- (Gulf Pub. Co., 1999)
Total Plant Performance Management (TPPM) is an unparalleled continuous-improvement program that integrates all plant functions into a single focused effort. The fundamental premise is that all corporate functions, from the boardroom to the shipping department, must share a common vision and effectively work together. This book details TPPM's proven method of implementing continuous improvement throughout your total corporation, not just in certain departments. It shows you how to promote, implement, and maintain continuous improvement; effectively involve all employees; train people the right.